2011
DOI: 10.3390/d3030453
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Stand Characteristics and Spatial Aggregation of Tree Species in a Bangladesh Forest Ecosystem

Abstract: Assessing biodiversity and the spatial structures of forest ecosystems are important for forestry and nature conservation. However, tropical forests of Bangladesh are only sparsely investigated. Here we determined biodiversity (alpha, beta and gamma), spatial species turnover and stand characteristics of one of the few remnant tropical forests in Bangladesh. Two differently protected areas of Satchari forest were compared. We recorded tree species composition, in a systematic plot design, measured diameter at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Nekola & White, 1999). Untransformed relations are problematic, as the fitted line intersects with the x ‐axis as well as with the y ‐axis implying negative similarity values after a certain distance and negative distances for specific similarity values (Uddin et al ., 2011). However, it has the advantage of a straightforward interpretation within the range of admissible values for similarity and distance.…”
Section: Methodsmentioning
confidence: 99%
“…Nekola & White, 1999). Untransformed relations are problematic, as the fitted line intersects with the x ‐axis as well as with the y ‐axis implying negative similarity values after a certain distance and negative distances for specific similarity values (Uddin et al ., 2011). However, it has the advantage of a straightforward interpretation within the range of admissible values for similarity and distance.…”
Section: Methodsmentioning
confidence: 99%
“…Anthropogenic interference is the primary driver leading to the geographic disparity in diversity of species in Bangladesh (Uddin, et al 2011). However, Satchari National Park (SNP) has a rich biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Ouédraogo et al (2019) in the tropical areas of Burkina Faso concluded that there is a strong positive relationship between fruit production, crown cover, and the recruitments of B. aegyptiaca seedlings and saplings. Tree species diversity, seedling and sapling density, recruitment and stand composition were strongly associated with mature tree basal area and the severity of human intervention, as well as abiotic factors in the area (Gebeyehu et al, 2019;Ghanbari et al, 2021;Hammond et al, 2021;Hasoba et al, 2020;Uddin et al, 2011). However, the currently observed lower density of Soil nitrogen, organic carbon, potassium, and phosphorus were all higher beneath trees growing in our undisturbed sites compared with the disturbed sites.…”
Section: (Ii) Lowest Seedling Sapling and Tree Density In The Disturb...mentioning
confidence: 57%
“…reported that 86% of Pinus sylvestris saplings in the natural forests at the Mediterranean mountains had been browsed several times by goats within the same season, and their growing shoots are continuously browsed, particularly during the dry season where herbaceous plants are scare. Besides that,Sher et al (2010) andUddin et al (2011) have mentioned that nomadic grazing in Pakistan and India had suspended the species diversity to less than 10%, and many medicinal and fodder tree species had disappeared. The lower recovery of B. aegyptiaca saplings in the DBR shows their sensitivity to livestock browsing, especially intensive ones.…”
mentioning
confidence: 99%